Glazing with conductive coating and printed layer, method of producing same and method of using same - Patents.com

By printing coatings with specific surface roughness on vehicle glass and combining conductive coatings and electric busbar, the problem of uneven thermal distribution of existing vehicle glass conductive coatings is solved, achieving efficient thermal management and temperature control.

JP7654651B2Active Publication Date: 2025-04-01PILKINGTON GRP LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2022525537
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-01
Filing Date
2020-11-02
Publication Date
2025-04-01
Estimated Expiration
2040-11-02

AI Technical Summary

Technical Problem

The conductive coatings in existing vehicle glass have inhomogeneity in thermal distribution and conductivity, resulting in inefficient thermal management and cannot meet the needs of rapid heating and temperature control in different areas.

Method used

By printing a coating with a specific surface roughness on the glass surface, and combining a conductive coating with an electrical busbar, the area roughness of the coating is controlled to optimize conductivity and thermal management performance.

Benefits of technology

It realizes efficient thermal management of vehicle glass, and can achieve rapid heating or temperature control in different areas as needed, improving the overall performance of the glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654651000003
    Figure 0007654651000003
  • Figure 0007654651000004
    Figure 0007654651000004
  • Figure 0007654651000005
    Figure 0007654651000005
Patent Text Reader

Abstract

The present invention provides glazing 1 comprising a first glass sheet 2 having a printed layer 3 on a portion of a surface of the glass sheet 2 and a conductive coating 6 on a surface of the first glass sheet 2. The conductive coating 6 extends onto at least a portion of the printed layer 3 to form a coated printed portion 7 and onto a portion of the surface of the glass sheet 2 to form a coated glass portion 8. The coated printed portion 7 has an interfacial developed area ratio Sdr of less than 27.45%. Methods for manufacturing the glazing and for using the glazing in a vehicle are also disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to glazing comprising an electrically conductive coating and a printed layer, a method for producing same and its use (eg as laminated vehicle glazing). [Background technology]

[0002] Single sheet or laminated glazing is useful as vehicle glazing. Laminated glazing, which comprises two or more glazing materials (usually glass) bonded together using a bonding polymer, is particularly useful as windshield or rear glazing.

[0003] Such glazing may have mist elimination and / or de-icing functions provided by electric heating. Parts of the glazing may require variable heating, for example by more rapid heating of the wiper rest area or the part of the glazing where the camera is located (as part of an advanced driver assistance system, ADAS).

[0004] To produce a vehicle glazing having an electrically conductive region, an electrically conductive coating can be provided on at least one of the surfaces of the glass sheet or the plies of the laminate. The electrically conductive coating also advantageously provides solar control properties to the glazing.

[0005] Conductive coatings for use in glazing heating applications typically comprise at least one silver layer disposed between dielectric layers. Such a layer may be deposited on the surface of at least one ply by a vacuum coating process, e.g., sputtering. The coating may be deposited before or after forming of the glazing.

[0006] Conductive coatings for use in heating applications have bus bars, usually located along the edges of the conductive coating, that are in electrical contact with the conductive coating and serve to connect the conductive coating to a power source (usually a vehicle power source).

[0007] US Patent 2,710,900 (Linder) discloses a vehicle glazing in which spaced bus bars on a glass sheet are covered with a conductive film. Intermediate the bus bars is a conductive aid having a higher electrical conductivity than the film to control the resistance between the bus bars.

[0008] U.S. Patent Application Publication No. 2006 / 0186105 (Voeltzel) discloses a laminated vehicle glazing. A busbar assembly is on the inner surface of an outer glass ply. A conductive coating is deposited over the busbar assembly and a portion of the glass. A decorative band is on the inner surface of the inner glass ply. The decorative band forms an opaque border around the glazing to hide a portion of the busbar assembly.

[0009] US 2017 / 0135160 (Masschelein) discloses a laminated vehicle glazing having a conductive coating, a masking strip and a copper foil busbar. The conductive coating deposited on the masking strip formed in a conventional manner by screen printing has a sheet resistance of 4 Ω / □. The coating deposited on the masking strip formed by an inkjet method of spraying droplets has a sheet resistance of 2 Ω / □.

[0010] In summary, a dark colored obscuring band (decorative band or masking strip) is usually provided on vehicle glazing in the form of a printed layer towards the edge of the glazing so that the busbars are not visible. The obscuring band may be formed from an enamel ink that is printed onto the surface of the glass ply, may be pre-fired at 400-680°C, and then bent to shape. Firing may occur simultaneously with the shaping of the glass ply, and as mentioned above, a conductive coating may be deposited on the surface of the glass ply and on the surface of the printed layer. In laminated glazing, the conductive coating, busbars and obscuring band may be deposited on surface 2, which is the inner surface of the laminate that contacts the polymer interlayer and the outer glass ply.

[0011] Variations in the electrical conductivity of the conductive coating can be problematic and can lead to hot spots and inefficient use of power. It is advantageous to design the conductive coating to ensure efficient heat distribution throughout the heated glazing and to allow parts of the glazing to be heated more quickly or to different temperatures if necessary (e.g., heated wiper rest areas, HWRA). Thus, there is a need to provide an improved glazing with a predetermined heat distribution. The object of the present invention is to address that need. Summary of the Invention

[0012] Thus, the present invention provides in a first aspect a method for producing a method for treating a cancer comprising the steps of: A first glass sheet having a printed layer on a portion of a surface of the glass sheet; a conductive coating on a surface of the first glass sheet, the conductive coating extending over at least a portion of the printed layer to form a coated printed portion and over a portion of the surface of the glass sheet to form a coated glass portion; Here, the coated printed portion provides a glazing having an interfacial developed area ratio Sdr of less than 27.45%.

[0013] The inventors have discovered that by controlling the area measurement of the roughness of the coated print, the desired sheet resistance can be obtained and optimal process conditions found.

[0014] This is highly advantageous as it provides the ability to easily vary the heating distribution within the glazing by selecting a given area measurement of the roughness of the coated printed part.

[0015] Coated printed parts may be combined with bus bars and external circuitry to provide further advantageous embodiments. The present invention teaches how to select optimal conditions for the manufacturing process for the selection of inks, baking times and baking temperatures.

[0016] By configuring the coated printed portion with a selected area roughness measurement using a bus bar, the coated printed portion becomes a heater of predetermined power to a desired zone of the glass sheet.

[0017] The inventors have overcome the prior art technical prejudice (e.g., U.S. Patent Application Publication No. 2017 / 0135160) that the sheet resistance of a coated printed part is controlled by a linear measurement of the roughness Ra of the printed layer. The inventors have discovered that areal measurements of the roughness, Sa, Sdq or Sdr, of a coated printed part have a better correlation with sheet resistance, believed to be due to a better measurement of the surface microstructure.

[0018] Preferably, at least two printed bus bars are provided for supplying power to the conductive coating, each bus bar being in electrical contact with a conductive coating.

[0019] Printing the busbars is highly advantageous as it improves the contact between the busbars and the coated printed part.

[0020] Preferably, the sheet resistance of the coated printed part is in the range of 2 to 200 Ω / □, more preferably in the range of 2.5 to 120 Ω / □, and most preferably in the range of 3 to 8 Ω / □.

[0021] The coated printed portion may have an areal roughness Sa in the range of 0.15 μm to 0.30 μm. Preferably, the coated printed portion has an interfacial developed area ratio Sdr in the range of 5 to 25%. The surface of the printed layer 3 preferably has a root-mean-square slope Sdq in the range of 4° to 30°, preferably in the range of 5° to 25°.

[0022] The coated printed part may have an average roughness Ra greater than 0.5 μm, preferably greater than 0.6 μm, more preferably greater than 0.7 μm, more preferably greater than 0.8 μm, and most preferably greater than 0.9 μm.

[0023] The inventors measured the average roughness Ra using a profilometer with a stylus tip radius of 2-10 μm and found poor correlation with sheet resistance. The inventors measured the developed area ratio Sdr of the interface using an AFM with a tip radius of 2-20 nm and found good correlation with sheet resistance. The sheet resistance of the conductive coating on the printing layer is believed to be controlled by the microstructure of the coating surface, which can be measured by AFM but not by profilometer.

[0024] The inventors have found that the sheet resistance of the coated glass portion is typically less than the sheet resistance of the coated printed portion. The sheet resistance of the coated glass portion may be in the range of 0.5-4.5 Ω / □, more preferably in the range of 1.0-4.0 Ω / □. The sheet resistance of the coated printed portion may be at least 20% greater or less than the sheet resistance of the coated glass portion, preferably at least 50% greater than the sheet resistance of the coated glass portion, more preferably at least 100% greater than the sheet resistance of the coated glass portion.

[0025] To mask the busbars and edges of the glazing (when used), the printed layer will typically be an obscuring band located towards the periphery of the glazing. Preferably, the printed layer acts to obscure the peripheral areas of the glazing and therefore preferably the printed layer has a visible light transmission (ISO 9050 Vis) of 0.1% or less, more preferably 0.05% or less.

[0026] The printing layer may be formed of an enamel ink comprising an inorganic pigment and a frit. Typically, the enamel ink comprises a pigment (usually black) having particles with an average particle size of more than 5.2 μm. Typically, the enamel comprises 10 wt% to 50 wt% of an inorganic pigment and 20 wt% to 80 wt% of a frit. The oxide frit may include particles of at least one compound selected from silica, titanium oxide, alumina, zirconia, compounds having fluoride ions (e.g., fluorite, fluoroapatite, cryolite, etc.), bismuth oxide, zinc oxide, boron oxide, potassium oxide, sodium oxide, calcium oxide, barium oxide, lead oxide, lithium oxide, phosphorus oxide, molybdenum oxide, strontium oxide, and magnesium oxide. Suitable inorganic pigments may comprise Fe / Cr pigments, Co / Al pigments, Co / Al / Cr pigments, Co / Ti pigments, Co / Cr pigments, Ni / Fe / Cr pigments, Ti / Cr / Sb pigments, Fe pigments, Cr pigments and / or mixtures of two or more of these pigments.

[0027] (Example of enamel ink) Infrared drying glass enamel ink 1L5350-WF803# is a suspension of frit and inorganic pigment in an organic medium of solvent and resin. The solvent is 2-(2-butoxyethoxy)ethanol. The resin is a polyamine amide salt. The solids content is 86.5%. It is available from Johnson Matthey Advanced Glass Technologies BV, Fregatweg 38, 6222 NZ Maastricht, The Netherlands.

[0028] Infrared drying glass enamel ink 1EPB2020-WF733P is a suspension of frit and inorganic pigment in an organic medium of solvent and resin. The solvent is 2-(2-butoxyethoxy)ethanol. The resin is a 1,2-ethanediamine polymer with aziridine. The solids content is 84.6%. It is available from Johnson Matthey Advanced Glass Technologies BV, Fregatweg 38, 6222 NZ Maastricht, The Netherlands.

[0029] Other suitable ink types from Johnson Matthey include RD1379, RD100, IT3015.

[0030] Ceramic coating ink 1401936 (14 316 IR-9876-C) is a suspension of frit and inorganic pigments in organic solvents glycol ether / acetate and alcohol. It is available from Ferro GmbH, Gutleutstraße 215, 60327 Frankfurt am Main, Germany.

[0031] Glass enamel ink YD-WA607 is a suspension of frit and inorganic pigments in an organic medium of solvent and resin. The frit is Bi 2 O 3 -B 2 O 3 -SiO 2 , 35-60%. Inorganic pigments are Cr 2 O 3 , CuO, MnO 2 , Co 2 O 3 The composition is ZnO, 20-35%. The solvent is terpineol, 15-20%. The resin is cellulose resin, 1-10%. Available from Shenzhen Octopus Technology Co., Ltd, No. 9 Octopus Building, Yuanling Industrial Park, Tianxin Blvd,,Baoan District, Shenzhen, China.

[0032] Cobalt, preferably as an oxide, is not only a pigment but also provides an anti-blocking function that is particularly useful in the AdvancedPressBend™ forming process. Particle size may also be selected for the anti-blocking function.

[0033] Advantageously, the conductive coating is a solar control coating comprising multiple coating layers, and is preferably a sputtered solar control coating (ie formed by sputtering, typically magnetron sputtering).

[0034] The conductive coating may comprise at least one infrared reflective layer, preferably silver, If higher conductivity or improved solar control is desired, the conductive coating may comprise two or three infrared reflective layers, usually silver.

[0035] The conductive coating typically comprises a plurality of dielectric layers, with each infrared reflective layer disposed between at least two dielectric layers. Each dielectric layer may comprise a material selected from tin oxide, zinc oxide, zinc stannate, aluminum nitride, silicon nitride, or a mixture of two or more of these materials.

[0036] To provide a more durable coating, the conductive coating may include at least one protective layer, which may optionally comprise titanium, niobium, or a mixture of titanium and niobium.

[0037] The printed busbar may contact the coated printed portion or may further include an additional busbar for heating the coated glass.

[0038] An advantage of the present invention is that the use of a coated printed portion with a predefined sheet resistance allows for great design freedom to control the heating of a portion of the glazing. Thus, preferably, the printed busbar and the coated printed portion are configured such that the coated printed portion heats a desired zone of the glass sheet. Thus, the glazing may comprise a wiper rest area or a camera area, and the coated printed portion may be positioned and adapted to heat the wiper rest area or the camera area.

[0039] The coated printed parts and the coated glass may be configured as components of a series or parallel circuit.

[0040] The properties of the print layer can be altered to affect a given sheet resistance of the coated printed part. Thus, the print layer can be formed such that it has patterned portions, with dots, lines, faded out or feathered edges or other patterns as desired.

[0041] Additionally or alternatively, the printing layer may further comprise an overprint layer comprising a conductive print, optionally a silver-containing conductive print, to adjust the sheet resistance of the coated printed portion either before or after the conductive coating is applied. The overprint may also be formed to have patterned portions, optionally comprising dots, lines, faded out or feathered edges or other patterns. Preferably, the overprint comprises silver printed dots. In one embodiment, the conductive coating on the printing layer had a sheet resistance of 15 Ω / □. On the same printing layer, a pattern of silver dots was applied by printing, and then the same coating was applied by sputtering, and the resulting product had a sheet resistance of 3 Ω / □.

[0042] In glazing, it can be useful if the glass sheets are tempered glass sheets.

[0043] The glazing may be laminated glazing, in which case the glazing may further comprise a ply of interlayer material disposed on the glass sheet and a second glass sheet disposed on the ply of interlayer material to form the laminated glazing, The ply of interlayer material may comprise polyvinyl butyral (PVB).

[0044] The present invention may provide a vehicle window comprising a glazing according to the first aspect.

[0045] The present invention provides in a second aspect a method for producing a glazing, the method comprising the steps of: Providing a first glass sheet; providing ink to a portion of a surface of a glass sheet to print a printing layer; baking the ink of the printing layer for a baking time in the range of 80 to 180 seconds and at a temperature in the range of 500°C to 695°C; depositing a conductive coating on a surface of a first glass sheet, the conductive coating extending over at least a portion of the printed layer to form a coated printed portion and over a portion of a surface of the glass sheet to form a coated glass portion; Including, Here, the ink, baking time and baking temperature are selected such that the coated printed part has an interfacial developed area ratio Sdr of less than 27.45%.

[0046] Preferred embodiments of the second aspect of the invention are generally as discussed in relation to the first aspect, with appropriate mutatis mutandis.

[0047] The ink for the printing layer is baked at a baking temperature in the range of preferably 500 to 680°C, more preferably 620 to 670°C, and most preferably 620 to 640°C or 640 to 660°C.

[0048] Preferably, the method includes printing at least two bus bars for supplying power to the conductive coating, each of the two bus bars being in electrical contact with the conductive coating, the printing of the bus bars being either before or after the deposition of the conductive coating.

[0049] The inventors believe that the surface microstructure is revealed by porosity testing during the manufacturing process, where water is applied and the water absorption by the surface is visually assessed. From porosity testing and gloss measurements, the inventors have found that porosity is more dependent on firing temperature than on firing time.

[0050] At low temperatures, the printed ink particles do not fuse properly, resulting in high porosity. At high temperatures, the printed ink layer crazes and cracks, resulting in high porosity. At intermediate temperatures, the printed ink cures optimally, resulting in low porosity. The inventors have found that low porosity is associated with a smooth surface microstructure and therefore low sheet resistance.

[0051] The glazing according to the invention finds use in many applications, including as vehicle glazing. Thus, in a third aspect, the invention provides the use of a glazing according to the first aspect, which may be in a vehicle, a building, an electronic display or a white goods appliance (e.g. a refrigerator or freezer).

[0052] The invention will now be described, by way of example only, with reference to the accompanying drawings, in which like reference numbers identify like parts throughout, and in which: [Brief description of the drawings]

[0053] [Figure 1] FIG. 1 is a plan view of a glazing or window according to the present invention having one heater. [Diagram 2] FIG. 2 is a cross-sectional view of the glazing of FIG. 1 taken along line AA. [Diagram 3] FIG. 2 is an alternative cross-sectional view of the glazing of FIG. 1, where the busbar is on the print. [Figure 4] FIG. 2 is a plan view of another glazing according to the present invention having two heaters connected in series. [Diagram 5] FIG. 13 is a plan view of another window according to the present invention having three bus bars. [Figure 6] FIG. 2 is a circuit diagram of the window of FIG. 1. [Figure 7] FIG. 5 is a circuit diagram of the window of FIG. 4. [Figure 8] FIG. 6 is a circuit diagram of the windows of FIG. 5 wired in series. [Figure 9] FIG. 6 is a circuit diagram of the windows of FIG. 5 wired in parallel. [Figure 10]1 is a graph of the sheet resistance of coated printed parts as a function of interfacial developed area ratio (Sdr) up to 8 Ω / □. [Figure 11] 1 is a graph of the sheet resistance of coated printed parts as a function of interfacial developed area ratio (Sdr) up to 120 Ω / □. [Figure 12] 1 is a graph of gloss (at a 60° viewing angle) of a coated printed part as a function of baking time of the printed layer at 695° C. Gloss varies as an areal measure of the roughness of the coating. High gloss generally indicates a smooth surface microstructure and is associated with low porosity and low sheet resistance. [Figure 13] 1 is a graph of sheet resistance of coated printed parts as a function of firing temperature from 620 to 680° C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0054] With reference to Figure 1, the glazing 1 comprises a glass sheet 2. The glass sheet 2 may be soda-lime-silica glass formed by the float process and may have a thickness of 0.5mm to 25mm. The glass sheet 2 may be tempered or semi-tempered and may be monolithic. Optionally, a ply of interlayer material may be applied to the glass sheet 2 and a second glass sheet may be applied to the ply of interlayer material to form a laminated glass.

[0055] A printing layer 3 is printed onto the glass sheet 2. The printing layer may be an enamel as disclosed in US Patent Application Publication No. 2017 / 0135160 and may be applied by any known method, for example, screen printing or inkjet printing.

[0056] A conductive coating 6 is deposited on at least a portion of the printed layer 3 to form a coated printed portion 7. The conductive coating 6 may have multiple functional layers for electrical conductivity, infrared reflectance (IRR), low emissivity, transmission and reflection in the visible spectrum (Tvis, Rvis) and solar control. The functional layers may include a base dielectric of zinc oxide or zinc tin on zinc oxide deposited by sputtering (physical vapor deposition).

[0057] Laminated glazing can be generally produced as follows: a flat glass substrate (for example, soda lime float glass with a thickness of 2.1 mm) is subjected to printing, for example screen printing (for example using a screen that may have a polyester screen of 50 to 120 threads / cm, for example a polyester screen of 77 or 100 threads / cm), by silk screen and doctor blade with enamel ink, forming a screen-printed layer that serves as an obscuring band, which is optionally dried by exposing this substrate to infrared radiation from an infrared heater at a temperature of less than 300 ° C. Then, the two printed glass substrates for forming the outer glass ply 12 and the inner glass ply 14 are stacked and the stacked substrates are subjected to bending. At this stage, a heat source is provided and bending can be affected, for example, by heating to a temperature of 570 ° C for more than 8 minutes, held at this temperature for a baking time of 1 minute, and then bent at this temperature by pressing or sag bending in a bending mold or frame. The substrates are separated and after cooling are coated with a sputtered conductive coating and laminated using a PVB interlayer (approximately 0.76 mm thick).

[0058] The glazing may be laminated by a method, for example, first degassing the PVB layer with nip rollers or using vacuum rings applied to the edges of the first and second plies of glass. The first and second plies of glass and the PVB layer are laminated together in an autoclave at a pressure range of 6 bar to 14 bar and a temperature range of 110 to 150°C.

[0059] The conductive coating may generally be deposited as follows: The coating process is preferably carried out by setting appropriate coating conditions such that any oxygen deficiency of any oxide layer of the coating is kept low to achieve high light transmittance and color stability of the coated glass sheet during heat treatment.

[0060] The layers can be deposited on the glass sheet using conventional AC and / or DC magnetron sputtering equipment, with mid-frequency sputtering applied where appropriate. All dielectric layers of oxides of Zn and Sn (ZnSnOx, Zn:Sn ratio approx. 50:50 by weight) are deposited using Ar / O 2 The ZnO growth-promoting top layer of the lower antireflective layer was reactively sputtered from a zinc-tin target in an Ar / O sputtering atmosphere. 2 The features were sputtered from a Zn target in an Ar sputtering atmosphere without any added oxygen and with a residual oxygen partial pressure of less than 10 mbar. The barrier layers of (slightly substoichiometric and low optical absorption) Al-doped zinc oxide (ZnO:Al) were sputtered from a conductive ZnOx:Al target in a pure Ar sputtering atmosphere without added oxygen. In the case of TiOx barrier layers, the deposition process would preferably be controlled such that the oxygen content of the layers increases from the silver layer outwards. The base layer of the lower antireflective layer of aluminum nitride (AlNx) and the outer antireflective layer were each sputtered in an Ar / N sputtering atmosphere containing only residual oxygen. 2 The silicon nitride (SiNx) layers were reactively sputtered from an Al target in a sputtering atmosphere of 20Ar / N 2 It was reactively sputtered from an Al-doped Si target in a sputtering atmosphere.

[0061] The coating stack (double silver) has the following layers with thicknesses (given in nm): Glass / ZnOx 25nm-38nm Ag 8-10nm / TiOx blocker 1nm-3nm / ZnOx 77nm-89nm / Ag 10nm-12nm / TiOx blocker 1nm-3nm / ZnOx 31nm-38nm / SiO2:Al 4nm-6nm

[0062] The alternative coating stack, which is also dual silver, has improved conductivity, i.e. lower sheet resistance. Glass / ZnSnOx 22nm-32nm / ZnO:Al or ZnO 4nm-6nm / Ag 8-10nm / TiOx blocker 1nm-3nm / ZnSnOx 73nm-83nm / ZnO:Al or ZnO 4nm-6nm / Ag 10nm-12nm / TiOx blocker 1nm-3nm / ZnSnOx and / or ZnO:Al (or ZnO) 31nm-38nm / SiO2:Al 4nm-6nm

[0063] The glazing according to the invention is advantageous because it is possible to modify the sheet resistance of parts of the heatable glazing to provide a predetermined heat distribution, such that parts of the glazing are heated more quickly or to different temperatures.

[0064] Higher sheet resistance areas of the printed layer coating can increase the overall circuit resistance and reduce the overall heating power for a given voltage. This problem can be solved by selecting busbar locations, adding busbars, and placing switches as shown in the following example.

[0065] FIG. 6 is the circuit diagram of FIG. 1 and shows a coated printed part 7 supplied with a voltage V from first and second busbars 4, 5.

[0066] Figure 7 is the circuit diagram of figure 4 and shows the coated printed part 7 and the coated glass part 8 supplied with a voltage V from the first and second busbars 4, 5 in series such that the same current flows through each part. The power density of the coated printed part 7 is higher than the coated glass part 8 due to its higher sheet resistance and therefore its higher temperature. This operation can be exploited for example in a heated wiper rest area or in the part of the glazing 10 where the camera is located.

[0067] In contrast, the portions of the coated printed portion 7 to the left and right of the coated glass portion 8 have a lower power density than the coated glass portion 8 due to their higher sheet resistance, and therefore a lower temperature.

[0068] Figures 8 and 9 are circuit diagrams of Figure 5. The coated printed part 7, which extends over the entire width of the conductive coating 6, is fed from the first and second busbars 4, 5. The coated glass part 8 and the remaining part of the coated printed part 7 on the left and right sides and on top of the coated glass part 8 are fed from the second busbar 5 and the additional busbar 9. The power density and temperature of the coated printed part 7 is higher than that of the coated glass part 8. This operation can be utilized, for example, in the heated wiper rest area or in the part where the camera is located.

[0069] In Figure 8, the coated printed portion 7 and the coated glass portion 8 are connected in series so that a voltage (V) is applied through a first switch and shared between them. If required, a second switch is connected across the coated glass portion 8 and closed for rapid heating of the coated printed portion 7 which is used as a heated wiper rest area.

[0070] In FIG. 9, the coated printed portion 7 and the coated glass portion 8 are connected in parallel so that a voltage (V) is applied independently to each of them via first and second switches.

[0071] By changing the shape of the coated printed part 7, the heating current can be induced to achieve non-uniform heating of the glazing. For example, a large printed area of ​​sensors, called a sensor farm, can divert the current around the sensor farm, reducing the heating power of the sensor farm and advantageously increasing the temperature on both sides of it. EXAMPLES

[0072] Table 1 shows examples of areal measurements of sheet resistance and roughness according to the present invention. Samples 620-680 use Johnson Matthey ink type 1 EPB2020. Samples F18-F20 use Ferro ink type 14 316. Samples O1-O10 use Octopus ink type WA607.

[0073] [Table 1]

[0074] 10 and 11 are graphs of sheet resistance as a function of area measurements of roughness Sdr, showing that there is a correlation between area measurements of roughness and sheet resistance. By altering the surface microstructure by selecting an appropriate enamel ink and appropriate firing conditions (such as firing time and temperature), it is possible to control the surface microstructure of the printed layer and thus the sheet resistance of the coated printed part.

[0075] FIG. 12 is a graph of the gloss (at 60° C.) of the coated printed portion 7 as a function of the firing time (at 695° C.) of the printed layer 3 for a 3.1 mm thick glass sheet 2 having a printed layer screen printed using Johnson Matthey's durable anti-stick low melting point enamel (1T3015-WF789). Gloss (e.g., according to Standard Test Method for Specular Gloss, ASTM D523) is the specular reflection of a surface due in part to the surface microstructure. FIG. 12 shows that gloss can be controlled by varying the firing time of the enamel, at least in part due to the smooth microstructure of the surface. The optimal firing time is 145 seconds for a high gloss of the printed layer 3, which is associated with a low sheet resistance of the coated printed portion 7 of the finished product. This quantitative data supports the qualitative findings of the porosity test.

[0076] Figure 13 shows a graph of the sheet resistance of the coated printed part 7 as a function of the baking temperature of the printed layer 3 from 620 to 680°C. The ink type is Johnson Matthey 1EPB2020-WF733P as described above. The higher the baking temperature, the lower the sheet resistance.

[0077] For all samples in Table 1, a conductive coating 6 was deposited on a glass sheet 2 to form a coated glass portion 8 having a sheet resistance of 3.0 Ω / □. The sheet resistance was measured using a four-point method such as a Guardian Model SRM232 available from Bridge Technology (PO Box 9275, Chandler Heights AZ, 85127, USA).

[0078] Each of the samples in Table 1 had an uncoated area of ​​the printing layer 3 with an average roughness Ra of greater than 0.7 μm. Ra was measured using a profilometer with a stylus radius of 2 μm. For example, Talysurf™ is available from Taylor Hobson, PO Box 36, 2 New Star Road, Leicester, LE4 9JQ, UK.

[0079] Atomic force microscopy (AFM) measurements were performed using an AFM with a tip radius of 2-20 nm. For example, an AFM with Tapping™ mode and NanoScope™ software is available from Bruker UK Ltd (Banner Lane, Coventry, CV4 9GH, UK). AFM analysis of the samples was provided over an area of ​​5 μm × 5 μm on one region of each sample. Comparative Example

[0080] Table 2 shows comparative examples of sheet resistance and area measurements of roughness not in accordance with the present invention. Sample 610 uses Johnson Matthey ink type 1 EPB2020, as do samples 620-680.

[0081] Sample 610 was prepared by firing printed layer 3 at a firing temperature of 610° C. The Sdr of the coated printed portion 7 was 27.45% and the sheet resistance was 9.44 Ω / □.

[0082] [Table 2] Technical effects

[0083] Examples 620-680 can be configured as coated printed portions 7 to heat zones of glass sheet 2 because there is a surprising correlation between Sdr and sheet resistance as shown in FIG. 10. Comparative Example 610, however, is not as easily configured to heat zones because it has an undesirable step change to a higher sheet resistance. The coefficient of determination R2 for Comparative Examples 620-680 is 0.86. The R2 for the comparative examples is less than 0.82.

[0084] The comparative examples are not optimally cured and therefore define a threshold value of Sdr that is undesirable for obtaining a desired sheet resistance, a teaching not known in the prior art.

[0085] The inventors believe that the Sdr threshold represents the change in porosity of the printed substrate. The inventors have found that although gloss measurements also indicate porosity, Sdr is more reliable regarding the effect of porosity on sheet resistance.

[0086] Sdr is measured by AFM with a tip radius of 2-20 nm with fine structures on the order of 100 Angstroms. In contrast, conventional Ra is measured by profilometer with a stylus radius of 2 μm with coarse structures on the order of 10,000 Angstroms.

[0087] Surprisingly, other ink compositions selected to have Sdr below the same threshold also have a correlation between Sdr and sheet resistance, thus making the present invention possible independent of ink composition.

[0088] The method for producing glazing according to the invention selects the firing time and firing temperature such that the Sdr is below a threshold value. The method according to the invention is made possible without undue experimental burden by using porosity tests and gloss measurements for rapid feedback. Glazing with promising combinations of firing time and firing temperature are confirmed to be below the Sdr threshold using AFM. Definition

[0089] The Sa parameter is the areal roughness, expressed as the arithmetic mean height of the area in nm. It is an extension of Ra, the arithmetic mean height of the lines.

[0090] The Sdr parameter is the developed area ratio of an interface, expressed as the percentage of the additional surface area of ​​a defined area caused by roughness compared to that of a flat surface. A perfectly smooth surface has an Sdr of 0.

[0091] The Sdq parameter is the root mean square slope, calculated as the root mean square of the slope at all points within a defined domain. A perfectly smooth surface has an Sdq of 0. [Explanation of symbols]

[0092] 1 Glazing 2 Glass Sheets 3 printing layer 4 First busbar 5 Second busbar 6 Conductive Coating 7 Coated printed parts 8 Coated glass parts 9 Additional Busbars V Voltage

Claims

1. A glazing 1, A first glass sheet 2 having a printing layer 3 on a portion of a surface of the glass sheet 2; a conductive coating 6 on the surface of the first glass sheet 2, the conductive coating 6 extending over at least a portion of the printing layer 3 to form a coated printed portion 7 and over a portion of the surface of the glass sheet 2 to form a coated glass portion 8; wherein the coated printed portion 7 has an interface development area ratio Sdr of less than 27.45%; Glazing 1.

2. 2. The glazing of claim 1, comprising at least two printed busbars 4, 5 for supplying power to the conductive coating 6, the printed busbars 4, 5 each being in electrical contact with the conductive coating 6.

3. 3. Glazing according to claim 1 or 2, in which the surface of the printing layer 3 has an average roughness Ra of more than 0.5 μm, preferably more than 0.6 μm, more preferably more than 0.7 μm.

4. Glazing according to any one of claims 1 to 3, wherein the surface of the printing layer 3 has an interfacial developed area ratio Sdr in the range of 5 to 25%.

5. 5. A glazing according to claim 1 , wherein the sheet resistance of the coated glass portion (8) is less than the sheet resistance of the coated printed portion (7).

6. 6. A glazing according to any one of claims 1 to 5, wherein the sheet resistance of the coated printed portion 7 is at least 20% more or less than the sheet resistance of the coated glass portion 8, preferably at least 50% more than the sheet resistance of the coated glass portion 8, more preferably at least 100% more than the sheet resistance of the coated glass portion 8.

7. A glazing according to any one of claims 1 to 6, wherein the printed layer 3 is an obscuring band, preferably arranged towards the periphery of the glazing.

8. Glazing according to any one of the preceding claims, wherein the printing layer 3 is formed of an enamel ink comprising inorganic pigments and frits.

9. 9. The glazing of claim 8, wherein the enamel ink comprises a pigment having particles with an average particle size of greater than 5.2 μm.

10. 10. A glazing according to any one of the preceding claims, wherein the conductive coating 6 comprises at least one infrared reflective layer, preferably silver.

11. 11. The glazing of claim 10, wherein the conductive coating (6) comprises a plurality of dielectric layers, each infrared reflective layer being disposed between at least two dielectric layers.

12. Glazing as described in any one of claims 1 to 11, wherein the busbars 4, 5 further comprise an additional busbar 9 for contacting the coated printed portion 7 or for heating the coated glass 8.

13. 13. A glazing according to any one of claims 1 to 12, wherein the printed busbars 4, 5 with the coated printed portions 7 are configured such that the coated printed portions 7 heat desired zones of the glass sheet 2.

14. 14. A glazing according to any one of claims 1 to 13, wherein the printed layer 3 has patterned portions, optionally with dots, lines, faded out or feathered edges.

15. 15. A glazing according to any one of claims 1 to 14, wherein the printed layer 3 further comprises an overprint layer comprising a conductive print, optionally a silver-containing conductive print, to adjust the sheet resistance of the coated printed portion 7.

16. 16. The glazing according to any one of claims 1 to 15, wherein the glazing comprises a wiper rest area or a camera area, and the coated printed portion 7 is positioned and adapted to heat the wiper rest area or the camera area.

17. 17. A glazing as claimed in any one of the preceding claims, further comprising a ply of interlayer material disposed on the glass sheet 2 and a second glass sheet disposed on the ply of interlayer material to form a laminated glazing.

18. A vehicle window comprising a glazing according to any one of claims 1 to 17.

19. A method for producing a glazing 1, said method comprising the steps of: Providing a first glass sheet 2; providing ink on a portion of the surface of the glass sheet 2 to print a printing layer 3; baking the ink of the printing layer 3 for a baking time in the range of 80 to 180 seconds and at a baking temperature in the range of 500°C to 695°C; depositing an electrically conductive coating 6 on the surface of the first glass sheet 2, the electrically conductive coating 6 extending over at least a portion of the printed layer 3 to form a coated printed portion 7 and over a portion of the surface of the glass sheet 2 to form a coated glass portion 8; Including, wherein the ink, the baking time and the baking temperature are selected such that the surface of the printing layer 3 has an interface development area ratio Sdr of less than 27.45%; A method for producing a glazing 1.

20. A method for producing a glazing 1 according to claim 19, wherein the baking of the ink of the printed layer 3 is at a baking temperature in the range of 500 to 680°C, more preferably 620 to 670°C.

21. A method for manufacturing a glazing 1 according to claim 19 or claim 20, further comprising the step of printing two busbars 4, 5 for supplying power to the conductive coating 6, said two busbars each being in electrical contact with said conductive coating 6.

22. 18. Use of a glazing 1 according to any one of claims 1 to 17 in vehicles, buildings, electronic displays or white goods.

Citation Information

Patent Citations

  • Transpernent body capable of electric heating and its manufacture and manufacture of windproof glass capable of electric heating

    JP1990201887A

  • heated glass panel

    JP2017525643A